Factors of Competitive Advantage of Islamic Banks in Indonesia: A Literature Review Study - Robiah, Hesti Siti; Endarty, Kharisma; Nasim, Arim (Islamic Research, 2025)
This study explores the factors influencing the competitive advantage of Islamic banks in Indonesia through a systematic literature review (SLR). The study examines the development of the Islamic banking sector in Indonesia since the enactment of Law No. 7 of 1992 and highlights various aspects such as regulation, supporting infrastructure, public literacy, and supervision. Based on OJK data as of June 2023, Islamic financial assets reached IDR 2,450 trillion, with the Islamic capital market and Islamic banks as the largest contributors. The results show that the most significant factors influencing the competitive advantage of Islamic banks include the marketing mix, the role of technology, banking facilities, environmental influence, market orientation, training, infrastructure, the role of the government, service quality, Islamicity performance, online media marketing, customer relationship management (CRM), green banking, and intellectual capital. Most of the research uses quantitative methods (65%), followed by qualitative methods (33%) and mixed methods (7%). This study suggests that Islamic banks need to focus on these factors in their strategies to remain competitive in a dynamic and competitive market, with government support and the implementation of innovative technology as key success factors.